2016
DOI: 10.1016/j.matdes.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of residual stress, free volume, and hardness in the laser shock peened Ti-based metallic glass

Abstract: Laser shock peening (LSP) with different cycles was performed on the Ti-based bulk metallic glasses (BMGs). The internal residual stress of the LSPed specimens was measured by high-energy X-ray diffraction (HEXRD) and the residual stress on the shocked surface was measured by scanning electron microscope/focused ion beam (SEM/FIB) instrument. The internal residual stress in the LSP impact direction (about -170 MPa) is much lower than that perpendicular to the impact direction (about -350 MPa), exhibiting aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 40 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…The fatigue life of LSPed specimens was marginally improved at higher loads (see Figure 4c). Unchanged hardness values contrast with the expected softening typically induced by CRS [52,55]. This indicates that the stress state on the LSPed surface is still tensile, or slightly compressive.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The fatigue life of LSPed specimens was marginally improved at higher loads (see Figure 4c). Unchanged hardness values contrast with the expected softening typically induced by CRS [52,55]. This indicates that the stress state on the LSPed surface is still tensile, or slightly compressive.…”
Section: Discussionmentioning
confidence: 86%
“…LSP and SP have also been tested on BMGs to improve the ductility of the samples by inducing additional free volume, although not homogeneously [52][53][54]. Zhang et al [52] and Wang et al [55] reported softening close to the surface after applying SP and LSP, respectively, because of the induced free volumes. Raghavan et al [56] investigated the effect of shot peening on the fatigue life of a Zr-based metallic glass, and no significant improvement was reported.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of reports by Cao et al [23] and Wang et al [24] in the context of laser shock peening, and by Korsunsky et al [25] when synthesising a Zr-based BMG, this approach has rarely been employed for residual stress measurements in amorphous alloy research. It is expected that this technique is particularly suited for the current investigation of LSM-induced hardness modification because the literature suggests limited correlation between hardness and compressive residual stress in BMGs (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, MGs can be viewed as suitable candidates for investigating the underlying interaction between the shock wave and solid, due to the absence of dislocations, grain boundary and phase segregation. In addition, numerous experimental studies and computational simulations have revealed the existence of micro spatial heterogeneity in MGs, which could serve as a feasible structural indicator to evaluate their mechanical properties and deformation behavior [22][23][24]. These shock wave-induced microstructural fluctuations may also provide a new approach to gain a better understanding of the common laser-solid interactions.…”
Section: Introductionmentioning
confidence: 99%